Pengaruh Lama Penyimpanan dan Diameter Stum Mata Tidur terhadap Pertumbuhan Bibit Karet (Hevea brasiliensis Muell. Arg.) - Mitra Kasih Maruhawa; Asil Barus; T. Irmansyah (Universitas Sumatera Utara, 2015)
The purpose of this research is to found out the influence of storage period and diameter stump on stump rubber growth. This research was conducted at experimental field of Agriculture Faculty, University of North Sumatera, Medan, in april until august 2015, using randomized block design with two factors, i.e storage period (0,5,10,15,20 days) and diameter of stump (1.6-2.0 cm, 2.1-2.5cm, 2.6-3.0 cm). Parameters observed were percentage of grow, time of break bud, height of bud, diameter of bud, amount of leaf, total leaf area, root length, root dried weight and shoot dried weight. The result showed that the storage period significantly affected on percentage of grow, diameter of bud, amount of leaf, total leaf area and root length. While the treatment diameter of stump significantly affected on percentage of grow and root length. The interaction of two factor significantly affected on percentage of grow and root length.Keywords : stump rubber, storage period, diameter of stump